Microbial Evaluation of Cooked Foods Served in the Central Restaurant of Tehran University of Medical Sciences in Winter and Summer 2015 - Ali Salehi; Gholamreza Jahed Khaniki; Kaveh Shoghi; Daryoush Sanaei; Ehsan Haghi (Iranian Journal of Health, Safety and Environment, 2016)
Food-borne pathogens are the most important thing cause of illness and death in developing countries. Food safety is essential for central university kitchens because of the high number of meals served every day. These central university kitchen systems are of special interest as students are at relatively high-risk of developing serious complications from exposure to food bacterial contamination hazards. A total of 144 samples of cooked foods, collected in winter and summer 2015 from the restaurants of Tehran University of Medical Sciences, were studied to determine the microbiological quality of these products. Results were analyzed through SPSS 22.0 and t-test. According to coliform count, the highest rate of contamination was in Kebab (1.17×102 CFU/g) and lowest was in fish (0.8×102 CFU/g) and also the highest rate of contamination of Escherichia coli (E.coli) was in Kebab (6 samples), and the lowest contamination level was in fish and in this regard no sample was reported to be positive. According to staphylococcus aureus, the highest contamination rate was in rice (0.97×102 CFU/g) and lowest was in fish (0.63×102 CFU/g). Kebab had the highest contamination of ‎coliforms and staphylococcus aureus (S. aureus) in summer. None of the tested samples was confirmed with respect to salmonella, clostridium perfringens and staphylococcus aureus. Among the foods served in the university restaurants, Kebab had the highest bacterial contamination and fishes the lowest. Improved methods of cooking and food processing, prevention of secondary bacterial contamination, continuous monitoring and surveillance of food processing are the most important measures to prevent food contamination.